2016
DOI: 10.1002/anie.201601784
|View full text |Cite
|
Sign up to set email alerts
|

Well‐Defined Models for the Elusive Dinuclear Intermediates of the Pauson–Khand Reaction

Abstract: The mechanism of the Pauson-Khand reaction has attracted significant interest due to the unusual dinuclear nature of the Co2 (CO)x active site. Experimental and computational data have indicated that the intermediates following the initial Co2 (CO)6 (alkyne) complex are thermodynamically unstable and do not build up in appreciable concentrations during the course of the reaction. As a consequence, the key steps that control the scope of viable substrates and various aspects of selectivity have remained largely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 38 publications
0
22
0
Order By: Relevance
“…The successful isolation of the η 2 ‐alkene‐µ‐alkyne‐Co 2 (CO) 5 complexes 2 that represent the first fully characterized examples of the initial phase of the Pauson–Khand reaction,, prompted us to investigate a potentially more flexible system that could yield either an intramolecular product, or possibly another intermediate in the PKR pathway . As noted above, 6 H ‐dibenzo[ a , e ]cyclooctatrien‐5‐one ( 6 , Figure ) was converted into the alkynyl‐Co 2 (CO) 6 complexes 8 (Figure and Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…The successful isolation of the η 2 ‐alkene‐µ‐alkyne‐Co 2 (CO) 5 complexes 2 that represent the first fully characterized examples of the initial phase of the Pauson–Khand reaction,, prompted us to investigate a potentially more flexible system that could yield either an intramolecular product, or possibly another intermediate in the PKR pathway . As noted above, 6 H ‐dibenzo[ a , e ]cyclooctatrien‐5‐one ( 6 , Figure ) was converted into the alkynyl‐Co 2 (CO) 6 complexes 8 (Figure and Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…The Ni 2 (C 6 H 6 )-(NDI) complex is a versatile catalyst precursor for a wide variety of transformations, including hydrosilylation, 78 alkyne trimerization, 79 and nitrene dimerization. 80 This dinickel system was also used to model several proposed steps in a Pauson−Khand reaction, such that a bound alkyne complex and a nickelacyclic product of oxidative cyclization (Scheme 7) were observed, 81 accomplishing a long-standing goal in organometallic chemistry. 82 Additionally, treatment of the nickelacycle with CO generated the desired cyclopentenone product in high yield.…”
Section: ■ Unsymmetrical Ligandsmentioning
confidence: 99%
“…In our previous studies, we identified alkynes as strongly coordinating ligands that could potentially displace norbornadiene following C–C reductive elimination (Figure a). Accordingly, addition of 1-phenylpropyne to solutions of 3 resulted in the release of free norbornadiene and the formation of the previously characterized [ i ‑Pr NDI]­Ni 2 (PhCCMe) complex 4 . With an equimolar stoichiometry of 1-phenylpropyne and 3 , the reaction does not reach full conversion but establishes a stable equilibrium after approximately 5 min ( K eq = 2.1).…”
Section: Strain-driven Dinuclear C–c Oxidative Additionmentioning
confidence: 97%